Interpretation of organic spectra - Ning, Yong-Cheng. (Singapore : John Wiley & Sons (Asia) Pte Ltd., 2011)
"Although there are a number of books in this field, most of them lack an introduction of comprehensive analysis of MS and IR spectra, and others do not provide up-to-date information like tandem MS. This book fills the gap. The merit of this book is that the author will not only introduce knowledge for analyzing nuclear magnetic resonance spectra including 1H spectra (Chapter 1), 13C spectra (Chapter 2) and 2D NMR spectra (Chapter 3), he also arms readers systemically with knowledge of Mass spectra (including EI MS spectra and MS spectra by using soft ionizations) (Chapter 4) and IR spectra (Chapter 5). In each chapter the author presents very practical application skills by providing various challenging examples. The last chapter (Chapter 6) provides the strategy, skills and methods on how to identify an unknown compound through a combination of spectra. Based on nearly 40 years researching and teaching experience, the author also proposes some original and creative ideas, which are very practical for spectral interpretation"--
"The merit of this book is that the author will not only introduce knowledge for analyzing nuclear magnetic resonance spectra including 1H spectra (Chapter 1), 13C spectra (Chapter 2) and 2D NMR spectra (Chapter 3), he also arms readers systemically with knowledge of Mass spectra (including EI MS spectra and MS spectra by using soft ionizations) (Chapter 4) and IR spectra (Chapter 5)"--
Includes bibliographical references and index.
Keywords: Spectrum analysis; Organic compounds -- Analysis; SCIENCE / Spectroscopy & Spectrum Analysis